Cat Disease Detection Expert System Application Using WML on Mobile Phone - Alex Rowena; Mispah Luiz (Yayasan Gema Bina Nusantara, 2023)
This research aims to find out how to implement the forward chaining method in an expert system. This research used observation methods, questionnaires, literature studies, and interviews conducted with experts, namely veterinarians. This interview was conducted in the form of an unstructured interview. The researcher used a PC (personal computer) as the hardware. The software used in this research is Notepad++ 6.1.6. The operating system that the author uses in research is Windows XP SP2. The research results show that using this expert system helps detect disease in animals by helping users consult by answering a series of questions based on visible disease symptoms, which in turn will lead to a series of answers leading to a particular disease. In the solutions section, you can find first aid measures and follow-up actions that pet owners are expected to take to help the animal recover. Adding knowledge, documentation, and development to this expert system can be done via the mobile phone available on the admin page, so there is no need to overhaul the existing system; just insert, delete, and update. Development can be carried out by people with authority to add symptoms, diseases, and solutions to diseases.